The influence of calcination temperature on iron oxide (α-Fe2O3) towards CO2 adsorption prepared by simple mixing method = Kesan suhu pengkalsinan ferum oksida (α-Fe2O3) disediakan melalui kaedah campuran ringkas terhadap penjerapan CO2 - Lahuri, Azizul Hakim; Yarmo, Mohd. Ambar; , Tengku Sharifah Marliza; Abu Tahari, Maratun Najiha; Samad, Wan Zurina; Yusop, Muhammad Rahimi; Mohamed Hisham, Mohamed Wahab; Dzakaria, Norliza (The Malaysian Analytical Sciences Society, 2016)
Synthesized iron oxide, α-Fe2O3 used for CO2 capturing was prepared by a simple mixing method and calcined at temperatures in a range of 350 – 850 °C. CO2 adsorption isotherms at 25 °C and 1 atm found that the sample namely s450 that calcined at 450 °C gave the highest CO2 adsorption activity with the adsorption capacity of 17.0 mgCO2/gadsorbent. Monodentate carbonate, bidentate carbonate and bicarbonates formation were observed on s450 through the IR spectra. The basicity of s450 was identified by chemisorption of CO-TPD which contains weak, medium and strong basic sites with CO total adsorbed amount of 1.99 cm3/g. It was found that s450 calcined at 450 °C has certain crystallite peaks that abruptly increased through the XRD diffractogram. The texture properties of s450 generated high porosity and more uniform sphere shape particle size with high surface area (50.5 m2/g). Furthermore, it is composed of trimodal distribution for pore size distribution curve desirable for CO2 adsorption.